Marriage, sexuality, and holiness: aspects of marital ethics in the Corpus Paulinum - R. Zimmermann (Acta Theologica)
A fundamental change in the understanding of marriage becomes apparent in the first century A.D., described by M. Foucault as the transition from a “matrimonial” to a “conjugal” marital concept. While early Christianity participated in this development, it also influenced it at decisive points and developed its own marital ethics. Through a consideration of philosophical (Musonius, Plutarch) and early Judaic (esp. Qumran, Jubilees) texts, this article outlines the marital concepts existing in the NT environment. In this context, the reciprocal community and the duration of the marital relationship are emphasized while sexuality remains wholly limited to reproduction. The core of the article offers a concrete analysis of texts from the Corpus Paulinum (1Cor 5-7; 1Thess 4:1-5; Eph 5:21-33), in which one can recognize, upon the backdrop of a traditional-hierarchical classification of man and woman, an equal and holistic relationship of the marital partners. Simultaneously – and here the Pauline texts extend beyond the borders of their environment – sexual intercourse is valued as an important component of the relationship between husband and wife. Here, the relationship of marriage, including the physical union of the marital partners, is theologically substantiated, and the frequently occurring semantics of “holiness” clearly plays a central role in the context of the marital texts. In the theologically substantiated union of the sexes one can recognize not only traditional, but especially Judaic forms of speech, created through the close interweaving of relationships between the sexes and the relationship with God. In addition, further norms that regulate early Christianity, such as the condemnation of adultery or the prohibition of divorce, become understandable in new ways.